Ovarian osseous metaplasia-a clinical mimicker of teratoma: a rare case report - Jadhav, Asawari B.; Raut, Sonal T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ossification in the ovary is an extremely rare occurrence, typically associated with mature cystic teratomas, osseous metaplasia in serous or mucinous neoplasms, or endometriotic (chocolate) cysts. Isolated osseous metaplasia in the absence of these conditions is exceptionally uncommon. We report a rare case of a 28-year-old female who underwent laparoscopic oophorectomy following clinical and radiological suspicion of a mature cystic teratoma. However, histopathological examination revealed osseous metaplasia occurring in the background of a polycystic ovary, with no evidence of teratomatous elements. The lesion, although benign, radiologically mimicked a malignant neoplasm, leading to surgical intervention. This case underscores the diagnostic challenge posed by ossified ovarian lesions, which may be indistinguishable from malignant tumors on imaging. Osseous metaplasia, particularly in the context of polycystic ovary, is a rare but benign condition. Recognition of this entity is crucial, as it may allow for conservative management with close follow-up, avoiding unnecessary surgical procedures, especially in young women where fertility preservation is a concern. Ossified ovarian lesions, though rare, should be considered in the differential diagnosis of calcified ovarian masses. Accurate histopathological diagnosis is essential to guide appropriate management and prevent overtreatment.